Proteomic analysis of articular cartilage shows increased type II collagen synthesis in osteoarthritis and expression of inhibin betaA (activin A), a regulatory molecule for chondrocytes. - Hermansson, M; Sawaji, Y; Bolton, M; Alexander, S; Wallace, A; Begum, S; Wait, R; Saklatvala, J (2004)
We show that proteomic analysis can be applied to study cartilage pathophysiology. Proteins secreted by articular cartilage were analyzed by two-dimensional SDS-PAGE and mass spectrometry. Cartilage explants were cultured in medium containing [35S]methionine/cysteine to radiolabel newly synthesized proteins. To resolve the cartilage proteins by two-dimensional electrophoresis, it was necessary to remove the proteoglycan aggrecan by precipitation with cetylpyridinium chloride. 50-100 radiolabeled protein spots were detected on two-dimensional gels of human cartilage cultures. Of 170 silver-stained proteins identified, 19 were radiolabeled, representing newly synthesized gene products. Most of these were known cartilage constituents. Several nonradiolabeled cartilage proteins were also detected. The secreted protein pattern of explants from 12 osteoarthritic joints (knee, hip, and shoulder) and 14 nonosteoarthritic adult joints were compared. The synthesis of type II collagen was strongly up-regulated in osteoarthritic cartilage. Normal adult cartilage synthesized little or no type II collagen in contrast to infant and juvenile cartilage. Potential regulatory molecules novel to cartilage were identified; pro-inhibin betaA and processed inhibin betaA (which dimerizes to activin A) were produced by all the osteoarthritic samples and half of the normals. Connective tissue growth factor and cytokine-like protein C17 (previously only identified as an mRNA) were also found. Activin induced the tissue inhibitor for metalloproteinases-1 in human chondrocytes. Its expression was induced in isolated chondrocytes by growth factors or interleukin-1. We conclude that type II collagen synthesis in articular cartilage is down-regulated at skeletal maturity and reactivated in osteoarthritis in attempted repair and that activin A may be an anabolic factor in cartilage.